From Hegemony to Competition Marine Perspecitves on Expeditionary Advanced Base Operations - Slater, Matthew R. (Marine Corps University Press (MCUP), 2022)
The end of the Cold War in 1991 brought the United States more than two decades of global leadership and prosperity. Neorealist international relations theory correctly predicted that hegemony, although the most stable power arrangement, is doomed to deteriorate as rising competitors band together to challenge the existing world order. As the United States pivots from hegemony to competition, the Department of Defense is adjusting its capabilities to confront the Chinese Communist Party and the Russian oligarchy. The U.S. Marine Corps may be considered at the forefront of the rapidly changing force structure. These changes will not rely on the acquisition of new weapons systems for success. Instead, the capacity of Marines to accommodate new ways of thinking, norming chaotic processes, and adapt to dynamic operational environments will determine their outcome. This volume provides a window into how current and future Marine leaders will grapple with this historic challenge.